Electrospinning in promoting chronic wound healing: materials, process, and applications - Kou, Jiaxi; Li, Yaodong; Zhou, Chen; Wang, Xiyu; Ni, Jian; Lin, Yue; Ge, Huaqiang; Zheng, Dongfeng; Chen, Guopu; Sun, Xitai; Tan, Qian (Frontiers in Bioengineering and Biotechnology, 2025)
In the field of wound treatment, chronic wounds pose a significant burden on the medical system, affecting millions of patients annually. Current treatment methods often fall short in promoting effective wound healing, highlighting the need for innovative approaches. Electrospinning, a technique that has garnered increasing attention in recent years, shows promise in wound care due to its unique characteristics and advantages. Recent studies have explored the use of electrospun nanofibers in wound healing, demonstrating their efficacy in promoting cell growth and tissue regeneration. Researchers have investigated various materials for electrospinning, including polymers, ceramics, carbon nanotubes (CNTs), and metals. Hydrogel, as a biomaterial that has been widely studied in recent years, has the characteristics of a cell matrix. When combined with electrospinning, it can be used to develop wound dressings with multiple functions. This article is a review of the application of electrospinning technology in the field of wound treatment. It introduces the current research status in the areas of wound pathophysiology, electrospinning preparation technology, and dressing development, hoping to provide references and directions for future research.